PENGARUH ATRIBUT PRODUK WISATA TERHADAP KEPUASAN WISATAWAN NUSANTARA KE PANTAI MELASTI, BADUNG PADA MASA PANDEMI COVID-19 - Huda, Farhanul; Dewi, NGAS.; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
This study focuses on the influence of tourism product attributes on the satisfaction of domestic tourists visiting Melasti Beach Tourist Attractions during the Covid-19 Pandemic. Attractions, facilities and accessibility are important attributes in tourism areas to shape and increase or maintain tourist satisfaction for the long term and sustainable. The purpose of this study is to determine the effect of Tourism Product Attributes (Attraction, Amenity, Accessibilities) on the satisfaction of domestic tourists who visit Melasti Beach Tourist Attractions during the Covid-19 Pandemic. This study uses a non-probability sampling technique with a special technique of purposive sampling. The sampling technique used in this research is online using google form. The number of samples in this study were 100 samples, which were determined based on the slovin formula with the number of domestic tourists visiting Melasti Beach. The analysis technique in this research is quantitative descriptive analysis. The results of the study based on the results of the t test showed that partially the attraction and facility variables had a significant influence on the satisfaction of domestic tourists visiting Melasti Beach in Badung Regency during the Covid-19 Pandemic. Meanwhile, the accessibility variable does not have a significant effect on the satisfaction of domestic tourists visiting Melasti Beach in Badung Regency during the Covid-19 Pandemic. Based on the results of the F test, it shows that simultaneously the attributes of tourism products have a positive and significant effect on the satisfaction of domestic tourists who visit the Melasti Beach Tourist Attraction in Badung Regency during the Covid 19 Pandemic by 31% obtained from the results of the determination analysis.